Society participation in preservation of Kuda Lumping Dance in Kedungboto Village, Kendal Regency - Fadilah, Nur; Martitah, Martitah; Sunarjan, YYFR. (Universitas Negeri Semarang, 2022)
This research aims to analyze the existence of the Kuda Lumping art in Kedungboto Village; the society interprets the art of Kuda Lumping in Kedungboto Village; the society's participation in the preservation of the Kuda Lumping dance in Kedungboto Village. The research method in this study used a qualitative research method. The data collection method used observation, interviews, and observation. The test technique for determining the validity of the data was used triangulation. The data analysis technique used an interactive model carried out by data collection, data reduction, presentation, and verification. This research showed that: The existence of Kuda Lumping art in Kedungboto Village now it's growing and getting better in terms of appearance, clothes, equipment, and music. Society interprets the Kuda Lumping art as; some people consider Kuda Lumping as entertainment; some consider Kuda Lumping a tradition, and some consider Kuda Lumping a ritual. The society's participation in preserving the Kuda Lumping dance Turonggo Wahyu Budoyo and Turonggo Tresno Budoyo were very active and enthusiastic. The form of social participation was through the idea, energy, property, skills, and social participation.